Strategic labor relations management in modern organizations - Casademunt, Ana Maria Lucia 1980- (Advances in human resources management and organizational development (AHRMOD) book series, 2016)
This book is a pivotal reference source for the latest scholarly research on emerging human resource practices in relation to labor management, featuring innovative methods to remain competitive in the global business arena"--Provided by publisher